Symptom response and episodic disability of long COVID in people with spinal cord injury: a case-control study - Md. Feroz Kabir; Khin Nyein Yin; Ohnmar Htwe; Mohammad Saffree Jeffree; Fatimah Binti Ahmedy; Muhamad Faizal Zainudin; Sharmila Jahan; Md. Zahid Hossain; K. M. Amran Hossain; Md. Waliul Islam; Tofajjal Hossain (Public Library Science, 2024)
Background Spinal cord injury (SCI) is a consequence of significant disability and health issues globally, and long COVID represents the symptoms of neuro-musculoskeletal, cardiovascular and respiratory complications. Purpose This study aimed to identify the symptom responses and disease burden of long COVID in individuals with spinal cord injury. Methods This case-control study was conducted on patients with SCI residing at a specialised rehabilitation centre in Bangladesh. Forty patients with SCI with and without long COVID symptoms (LCS) were enrolled in this study at a 1:1 ratio according to WHO criteria. Result Twelve LCS were observed in patients with SCI, including fatigue, musculoskeletal pain, memory loss, headache, respiratory problems, anxiety, depression, insomnia, problem in ADL problem in work, palpitation, and weakness. The predictors of developing long COVID include increasing age (p<0.002), increasing BMI (p<0.03), and longer duration of spinal cord injury (p<0.004). A significant difference (p<0.01) in overall years of healthy life lost due to disability (YLD) for non-long COVID cases was 2.04±0.596 compared to long COVID (LC) cases 1.22±2.09 was observed.